Analisis peran guru dalam meningkatkan minat baca peserta didik di sekolah dasar - Kalista Rintang; Siti Istiyati; Hadiyah Hadiyah (Didaktika Dwija Indria, 2021)
The research was conducted to analyze the teacher’s role to increasing students reading interest. The teacher’s role is important because teacher guides, encourages, and monitors the students. Increasing students reading interest is important. Some students don’t like reading because of a lack of reading habits and affected by technological advances. This research is a qualitative research with descriptive methods and a case study approach. The research was conducted at Karangasem 3 Elementary School in 2020. The subject is the teacher. The data are obtained from the location, teachers, and students. The data are obtained from observation, interviews, questionnaires, and documentation. The data validity used source and technique triangulation. Analysis using interactive analysis techniques Miles and Huberman. The results showed that the teacher's role in increasing students reading interest was applied by creating, facilitating, motivating, evaluating, and dynamizing reading activities. As a creator, the teacher makes new ideas in reading, as a facilitator the teacher provides physical facilities (infrastructure) and non-physical (services) related to reading activities, as a motivator the teacher always encourages students, as a evaluator, teacher evaluates the achievement of reading activities, and as a teacher dynamic, making reading activities continuity.